Description of a new species of spider mite of the genus Tetranychus Dufour (Acari: Tetranychidae) from Peru - Escobar-Garcia, Hector Alonso [UNESP]; de Andrade, Daniel Júnior [UNESP]; Beard, Jennifer J.; Ochoa, Ronald (Les Amis d'Acarologia, 2023)
A new species of spider mite, Tetranychus algarrobus n. sp., is described and illustrated from Peru. It was found damaging the foliage of the native forest tree Neltuma piurensis (Fabaceae) in Piura, northwestern Peru.
Keywords: algarrobo; forest tree; phytophagous mite; taxonomy mites; Tetranychoidea